Dampak Kebijakan Makan Bergizi Gratis Prabowo-Gibran Terhadap Pola Redistribusi Sumber Daya: Tinjauan Ekonomi Politik Kabupaten Gunungkidul. - Susila Wahyuana, Jaka; Elvia Agustina, Sitha; Wahyu Ristyadi , ⁠Martinus; Supami; Agvina , Fadila; Sihite, Jerry (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2026)
The Free Nutritious Meals (MBG) policy launched by the Prabowo–Gibran administration is a strategic intervention to improve the quality of human resources by fulfilling basic rights to food and nutrition, while also addressing stunting and alleviating economic burdens. This study analyzes the impact of MBG on resource redistribution patterns in Gunungkidul Regency from a political economy perspective. Using a qualitative case study approach reinforced by literature review, this study applies the Lowi (redistributive policy), rent-seeking , and patronage frameworks. The results show that the MBG is a highly conflictual redistributive policy. Limited local supplies, particularly rice and supporting products, have prompted political elites to opt for centralized procurement for logistical efficiency. This decision has opened up opportunities for rent-seeking and patronage practices, whereby regional suppliers obtain strategic contracts with the support of local elites. As a result, financial redistribution is distorted because most of the program funds flow out of the region. Although the MBG has succeeded in achieving its social welfare objectives, the program has failed to promote local economic redistribution due to the marginalization of farmers and MSMEs. It is recommended that BUMP/BUMD be established as off-takers to break the rent-seeking chain..